Analisis sikap disiplin belajar peserta didik selama pembelajaran daring ppkn materi hak dan kewajiban - Wanda Priasthi; Hasan Mahfud; Matsuri Matsuri (Universitas Sebelas Maret, 2023)
The purpose of this research is to describe the learning discipline of fourth grade students of SDIT Salsabila 6 Magetan during online learning of Civics on rights and obligations. The research approach used in this research is a descriptive qualitative research design with a case study approach. Data collection techniques is interviews, and documentation. The data analysis technique of this research is based on the interactive analysis techniques of Miles and Huberman. Data validity by Triangulation of sources and use of reference materials. The results of the study indicate that Civics learning on rights and obligations is carried out online through Whatsapp media. Students have shown obedience to learning activities at school as a form of learning obligation for students. Students have not shown their activeness during learning. This is caused by learning materials that are easy to understand, factors that decrease enthusiasm for learning, signal problems, cellphones brought by parents, and online learning that is not yet oriented to students. These factors also affect the inaccuracy of students in completing assignments. During online learning, the rights of students are fulfilled. Students get material rights and obligations, get feedback, and rewards even though it has not been fully implemented.Kata kunci: Learning Discipline, Online Learning, PPKn, Elementary School